2021
DOI: 10.18805/lr-4416
|View full text |Cite
|
Sign up to set email alerts
|

​Bio-efficacy of Chemical Insecticides and Biopesticides against Gram Pod Borer, Helicoverpa armigera (Hubner) and Spotted Pod Borer, Maruca testulalis (Geyer) on Greengram, [Vigna radiata (L.) Wilczek]

Abstract: Background: Gram pod borer, Helicoverpa armigera (Hubner) and spotted pod borer, Maruca testulalis (Geyer) are important pod boring insects infesting the greengram, [Vigna radiata (L.) Wilczek] throughout the India. A number of synthetic insecticides are known to be effective against these borers but most of them have been phased out as a result of high toxicity to the pollinators and other biotic fauna, therefore, a group of new chemical insecticides with biopesticides have been tested for bioefficacy against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Similarly, an increase in grain yield (8.86 q/ ha) was obtained in spinosad treated green gram field by Singh and Singh (2019). The present findings are in agreement in Umbarkar and Parsana (2014), Yadav and Singh (2014), Kaushik et al (2016) and Meena et al (2022) who reported the maximum grain yield from spinosad treatment. Singh et al (2020) recorded the highest marketable yield in flubendiamide 20 WG @ 1.0 g/l (9.14 q/ ha) and spinosad 45 SC @ 0.3 ml/l (9.13 q/ ha).…”
Section: Effect Of Spinetoram 6% W/v + Methoxyfenozide 30% W/ V Sc On...supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, an increase in grain yield (8.86 q/ ha) was obtained in spinosad treated green gram field by Singh and Singh (2019). The present findings are in agreement in Umbarkar and Parsana (2014), Yadav and Singh (2014), Kaushik et al (2016) and Meena et al (2022) who reported the maximum grain yield from spinosad treatment. Singh et al (2020) recorded the highest marketable yield in flubendiamide 20 WG @ 1.0 g/l (9.14 q/ ha) and spinosad 45 SC @ 0.3 ml/l (9.13 q/ ha).…”
Section: Effect Of Spinetoram 6% W/v + Methoxyfenozide 30% W/ V Sc On...supporting
confidence: 92%
“…Similar reports were given by Yadav and Singh (2014) and Sonune et al (2010). Similarly, spinosad 45 SC was proved to be effective against Helicoverpa armigera Hubner and M. testulalis infesting greengram (Meena et al, 2022). Selvam et al (2020) stated that flubendiamide 480 SC recorded the lowest larval population of gram blue butterfly, Euchrysops cnejus Fab.…”
Section: Resultsmentioning
confidence: 99%
“…Stems are much branched, sometimes twining at the tips. Young stems are purple or green, and mature stems are greyish yellow or brown (Meena et al, 2021) [16] . Mung beans are recognized for their high nutritive value.…”
Section: Introductionmentioning
confidence: 99%
“…Stems are much branched, sometimes twining at the tips. Young stems are purple or green, and mature stems are greyish yellow or brown" [2].…”
Section: Introductionmentioning
confidence: 99%